The Analysis of Discourse Markers in Science Debate - Sari, Erka Indah (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study investigated discourse markers that occurred in the science debate by TJump and Nathan Thompson. This research aimed to determine the types of discourse markers that TJump and Nathan Thompson used and described their functions. The researcher used a descriptive-qualitative approach to answer research questions by using Schiffrin's theory (1987). The data was taken from utterances containing discourse markers from TJump and Nathan Thompson's debate that discusses globe vs. flat Earth. This research reveals that there were six types of discourse markers and 11 discourse markers, which have different functions, such as a marker of information management (oh); a marker of response (well); discourse connectives (and, but, or); markers of cause and result (so, because); markers of temporal adverbs (now, then); markers of information and participation (I know, I mean). The function of those discourse markers are a marker of information management to attract attention, a marker of response to create coherence, discourse connectives to connect more units, to mark contrasting units as option markers, a marker of cause and result as a complement, and subordinate ideas, markers of temporal adverbs are to show the relationship between time, markers of information and participation are as the transition of information state and indicate the speaker's orientation. The next researcher can use another theory to analyze discourse markers, especially discourse markers as fillers. This study focused only on the types and functions of discourse markers; the researcher can connect discourse markers to speech acts and use different theories.